Structural relationships between aspects of hotel service quality and their effect on tourist satisfaction - Norazah Mohd Suki, (Penerbit Universiti Kebangsaan Malaysia, 2012)

(untitled)
This study examines the impact of assurance, reliability, responsiveness, tangibles and empathy on the level of tourist satisfaction with hotel service delivery A questionnaire is distributed to 200 respondents who are patrons of hotels in the Federal Territory of Labuan, Malaysia and are familiar with their services. The resulting data is analyzed using Structural Equation Modeling (sEm) via AMOS 5.0. The findings support previous research and demonstrate that tourists 'satisfaction can be enriched by changes and improvements in hotel services significantly associated with empathy, tangibles, reliability, and responsiveness. The amount of empathy perceived serves as the best predictor of tourist satisfaction, followed by the extent of the discernible tangible benefits. By recognizing the impact of assurance, reliability, responsiveness, tangibles and empathy on tourist satisfaction with hotel service delivery tourism marketers and planners should be able to attract more tourists by placing greater emphasis on the key aspects of hotel service considered in this study